Muhadharah Sebagai Media Membangun Kompetensi Mubaligh - Fakhira, Nadiya Nadha; Sumijaty, Siti; Rojudin, Rojudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to find out how skills, knowledge and expertise regarding muhadharah are held at the Al-Ihsan Cibiru Hilir Bandung Islamic Boarding School as a medium for building missionary competence. This research uses the Rhetoric theory of Marcus Tulius Cicero. The research method used is a qualitative research method. The results of this research concluded that in the skills stage the students in muhadharah activities displayed their respective styles and characteristics in tabligh. In the knowledge stage, muhadharah has an impact on increasing the faith of the students, getting to know each other and strengthening ties in the dormitory environment. And finally, in the skills stage, muhadharah provides students with various skills such as expertise in the field of material, communication skills, rhetorical skills, and most importantly, skills in reading or understanding mustami'.